The Internal Picture of the Child’s Health Viewed in the Context of Parent-Child Relationship - Merenkovawati, V (KnE Life Sciences, 2018)
The main function of the internal picture of health (IPH) is the regulation of a person’s activity or behavior, and is aimed at maintaining the person’s health, illness prevention and illness resistance. There is one subject that continues to be insufficiently accessible to psychological research, i.e. the system of the parenting style adopted in a family and the IPH levels of their children. We can suppose that IPH is one of the major indicators of the health-oriented behavior, the latter being significantly influenced by the interfamily relationships and the parenting style. Methods: there were 82 primary school children who participated in the study. Along with the children, their mothers also took part in the research. Practically all of the fathers agreed to enroll in the study, but in fact only a few were actually involved, which was not enough to provide evidence-based conclusions. The IPH of the children and their parents was evaluated by means of a questionnaire (Nikolaeva et al., 2014). Upbringing styles were assessed by “The Analysis of Family Relationships” questionnaire (AFR method). We have shown that the better-developed the IPH is, the more likely it can signify a harmonious upbringing style. A low level of the parents’ emotional intelligence results n the predominance of indulging hyper protection parenting style which is considered ineffective. Keywords: the internal picture of health, parent-child relationship, parents, primary schoolchildren.